UNVEILING THE PATH TO SUSTAINABLE SUCCESS: THE NEXUS OF INTELLECTUAL CAPITAL, INNOVATION, AND SUSTAINABLE BUSINESS PERFORMANCE IN INDONESIAN MANUFACTURING COMPANIES - Putri, Yesa Amanda; Woodhead, Kimberley; Sofia, Irma Paramita (International Journal of Contemporary Accounting, 2024)
Unlocking sustainable success in the manufacturing sector, particularly within Indonesia's dynamic landscape, holds paramount importance. This study aims to provide empirical evidence elucidating the profound influence of intellectual capital on sustainable business performance in Indonesian food and beverage manufacturing firms listed on the Indonesia Stock Exchange from 2018 to 2022. Focusing on a selected population, through purposive sampling techniques yielded a sample size of 40, meticulously analyzed using Eviews12. Employing a quantitative research approach, panel data regression forms the methodological foundation, revealing both the direct and indirect effects of intellectual capital on sustainable business performance, with innovation serving as a mediating variable. Sustainable business performance is assessed through the Sustainable Balance Scorecard (SUSBAL), while Intellectual Capital is measured using the Modified Value-Added Intellectual Coefficient (MVAIC), and innovation is quantified using the Company Innovation Index (CII). Empirical findings unveil a significant positive correlation between intellectual capital (IC), innovation (INV), and sustainable business performance (SBP), highlighting the role of various intellectual assets in driving organizational resilience and success. Additionally, the study explores the indirect influence of intellectual capital on sustainable business performance through innovation as a mediating variable. The results demonstrate that intellectual capital significantly and positively impacts sustainable business performance through innovation as a partial mediator. This study contributes novel insights into the intricate interplay between intellectual capital, innovation, and sustainable performance, offering strategic guidance for managers and policymakers navigating the complexities of Indonesia's manufacturing landscape, thereby fostering enduring organizational success and resilience amidst evolving market dynamics.